2001, a space odyssey : with an epilogue: After 2001 - Clarke, Arthur C. (Arthur Charles), 1917-2008. (New York : New American Library, 1982)
The spacecraft Discovery travels to the far edge of the Solar System, seeking the origin of a strange monolith found on the Moon.
A Signet book.
"Based on a screenplay by Stanley Kubrick and Arthur C. Clarke."